Respuesta :

Answer:

see explanation

Step-by-step explanation:

The equation of a line in slope- intercept form is

y = mx + c ( m is the slope and c the y- intercept )

Given

- 4x + 3y = 12 ( add 4x to both sides )

3y = 4x + 12 ( divide the terms by 3 )

y = [tex]\frac{4}{3}[/tex] x + 4 ← in slope- intercept form

with slope m = [tex]\frac{4}{3}[/tex] and y- intercept c = 4

---------------------------------------------------

Given

- 5x + 3y = - 9 ( add 5x to both sides )

3y = 5x - 9 ( divide the terms by 3 )

y = [tex]\frac{5}{3}[/tex] x - 3 ← in slope- intercept form

with slope m = [tex]\frac{5}{3}[/tex] and y- intercept c = - 3